Efficiency of Use of Labor Resources in Production Enterprises - Komilova Mukammal Shavkatovna; Mirzayev Zafar Abdialimovich (International Journal on Economics, Finance and Sustainable Development, 2022)
The article developed economically based proposals and recommendations for the provision of labor resources and effective use of production enterprises.